Heat wave tracker: A multi-method, multi-source heat wave measurement toolkit based on Google Earth Engine. (January 2022) - Zhang, Mingxi; Yang, Xihua; Cleverly, Jamie; Huete, Alfredo; Zhang, Hong; Yu, Qiang
Abstract: Under ongoing global warming due to climate change, heat waves in Australia are expected to become more frequent and severe. Extreme heat waves have devastating impacts on both terrestrial and marine ecosystems. A multi-characteristic heat wave framework is used to estimate historical and future projected heat waves across Australia. A Google Earth Engine-based toolkit named heat wave tracker (HWT) is developed, which can be used for dynamic visualization, extraction, and processing of complex heat wave events. The toolkit exploits the public long-term high-resolution climate datasets to developed nine heat wave datasets across Australia for extreme heat wave value analysis. To examine climate change on heat waves and how they vary in time and space, we also explore the probability and return periods of extreme heat waves over a period of 100 years. The datasets, toolkit and findings we developed contribute to global studies on heat waves under accelerated global warming. Highlights: A multi-characteristic heat wave framework is used to estimate historical and future projected heat waves across Australia. A Google Earth Engine-based toolbox was developed for dynamic visualization and processing of complex heat wave events. The toolkit provides nine heat wave datasets across Australia for extreme heat wave analysis. To examine climate change on heat waves, we also explore their probability and return periods over 100 years.